2005
DOI: 10.1007/s10750-004-1462-5
|View full text |Cite
|
Sign up to set email alerts
|

The ‘shock period’: dynamics of phytoplankton during the spring–summer transition of a stratifying English lake

Abstract: The spring to summer transition in a productive English lake is considered with respect to phytoplankton and its environmental conditions. Salient environmental changes include the onset of temperature/density stratification that is usually accompanied by a clear-water phase associated with a maximum of grazing Daphnia and a minimum of phytoplankton in the 0-5 m zone. Below this zone, as thermal stratification progresses, a deep maximum of phytoplankton can develop under strong thermal/density gradients and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…With C. marssonii there was insensitivity of rate over the even wider range of 8–25 °C, that is suggestive in relation to the seasonally widespread occurrence often found in the genus (e.g. Talling, Spencer & Morison, 2004). Other studies have found that for algal growth rates the temperature‐insensitive range varies considerably between species (Seaburg & Parker, 1983) but is typically wider than the corresponding range for short‐term photosynthesis (Jitts et al.…”
Section: Discussionmentioning
confidence: 69%
“…With C. marssonii there was insensitivity of rate over the even wider range of 8–25 °C, that is suggestive in relation to the seasonally widespread occurrence often found in the genus (e.g. Talling, Spencer & Morison, 2004). Other studies have found that for algal growth rates the temperature‐insensitive range varies considerably between species (Seaburg & Parker, 1983) but is typically wider than the corresponding range for short‐term photosynthesis (Jitts et al.…”
Section: Discussionmentioning
confidence: 69%
“…Salmaso et al, 2003;Teubner et al, 2003;Talling et al, 2005). During this growth period, P. rubescens might not only benefit from sufficient light and nutrient availability for autotrophic growth but also from low light-stimulated uptake of organic compounds released to the metalimnion after the breakdown of the phytoplankton spring peak.…”
Section: Climate Impactmentioning
confidence: 99%
“…, Gervais , Talling et al. , deNoyelles et al. ), i.e., they peak under conditions of reduced light and temperature.…”
Section: Discussionmentioning
confidence: 98%